Research on the application of post competency training for new nurses: current status and considerations - Yingxia, Li; Meiyao, Li; Jing, Bao; Aijuan, Zhao (Frontiers in Medicine, 2025)
The job competence of newly employed nurses is of crucial importance for nursing quality and patient safety. Nurse job competence emphasizes the comprehensive qualities of nursing knowledge, skills, attitudes, traits, and abilities that can achieve excellent work results in the actual nursing position and be competent for clinical nursing work. This article comprehensively analyzes relevant literature and elaborates on diverse training modalities for enhancing the job competency of newly recruited nurses. These encompass enhancements to conventional training approaches, simulation-based training, information-driven training, teamwork training, and scenario simulation cases. Additionally, it delves into the advantages, key implementation aspects, and associated challenges of these methods, with the objective of furnishing a reference for optimizing the training regimens of newly employed nurses.